1977
DOI: 10.1111/j.1365-2125.1977.tb00762.x
|View full text |Cite
|
Sign up to set email alerts
|

Ciclazindol and mazindol on glucose uptake into human isolated skeletal muscle: no interaction of mazindol with methysergide.

Abstract: 1 Ciclazindol, like mazindol, produced a significant concentration‐ dependent increase in glucose‐uptake into human skeletal muscle in both the presence and absence of insulin. 2 Methysergide, which inhibits the action of fenfluramine on glucose‐uptake into skeletal muscle, did not influence the effect of mazindol.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1979
1979
2007
2007

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 8 publications
(9 reference statements)
0
2
0
Order By: Relevance
“…Similarly to imipramine, et al, 1977;Kirby & Turner, 1977) is a tetra-ciclazindol antagonizes reserpine-and tetracyclic compound with activities very similar benazine-induced hypothermia in mice, potento those of established tricyclic antidepressants tiates metamphetamine-induced weight loss in 640 Felicity A. Kerr & E. Szabadi rats, and potentiates the noradrenaline-induced pressor response and the electrically induced contractions of the nictitating membrane in cats (Beckett et al, 1973).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly to imipramine, et al, 1977;Kirby & Turner, 1977) is a tetra-ciclazindol antagonizes reserpine-and tetracyclic compound with activities very similar benazine-induced hypothermia in mice, potento those of established tricyclic antidepressants tiates metamphetamine-induced weight loss in 640 Felicity A. Kerr & E. Szabadi rats, and potentiates the noradrenaline-induced pressor response and the electrically induced contractions of the nictitating membrane in cats (Beckett et al, 1973).…”
Section: Introductionmentioning
confidence: 99%
“…Mazindol increases glucose uptake into human isolated skeletal muscle (Kirby & Turner, 1976) as does fenfluramine, another well established weight-reducing drug (Kirby, 1974) in contrast to amphetamine which has no such effect (Kirby and Turner, 1974). Kirby and Turner (1977) have shown that ciclazindol, like mazindol, produces a significant concentrationdependent increase in glucose uptake into human skeletal muscle. This may indicate a metabolic mechanism underlying the weight loss in addition to appetite suppression.…”
Section: Introductionmentioning
confidence: 99%